LANTING OF RELIGIOUS VALUES THROUGH THE ROLE OF PARENTS IN A CHILDREN DURING COVID-19 IN DUKUH GEMUTRI SLEMAN YOGYAKARTA (International Conference on Social and Islamic Studies, 2021)
Religiosity (adjective religious) is not synonymous with religion. A religious person should be a religious person at the same time. Covid-19 has not only damaged people's lives in the health and economic fields, but religious activities in various regions have temporarily stopped carrying out worship activities in the mosque and surrounding areas, such asobligatory prayers, Friday prayers, yasinan, recitations, etc. Gemutri Hamlet, from the beginning of the Covid-19 outbreak, had confusion in deciding to carry out daily activities.This study uses a qualitative approach. The subjects of this study were the head of the hamlet, Mr. RW, Mr. RT, Pemuda, Karang Taruna, community leaders and some membersof the community. The object of this research is about the Internalization of Religious Values through the Role of Parents in Adolescents During Covid-19 in Dukuh Gemutri, Sleman, Yogyakarta. The technique used in determining the subject of this research isusing purposive technique and using snowball sampling method. Data collection techniques with observation, interviews and documentation. Data analysis techniques arecarried out by means of data reduction, data presentation, and drawing conclusions. Based on the results of the analysis and discussion of the process of Internalizing Religious Values through the Role of Parents in Adolescents During Covid-19, in Gemutri Hamlet, Sleman, Yogyakarta, it is very different from before the covid pandemic and after the pandemic, because at the beginning of the covid pandemic yesterday the community very scared and religious activities such as Mujahadah, Yasinan, etc., all of which were temporarily suspended but the very interesting thing in the Gemutri Sukoharjo hamlet community, Ngaglik Sleman, when there was Covid in the instilling of religious values, namely that usually there was no tasbih prayer activity, tasbih prayer was performed, when praying Friday in Friday prayers using the Qunud prayer and carrying out Istighosah activities